Nicaragua’s indispensable migrants and Costa Rica’s unconscionable new law - Cortés Ramos, Alberto (2006)
Those who criticize Costa Rica’s new immigration law are dismissed as advocating an unrestricted open door policy. This fallacy is just one more attempt to legitimize a law that violates basic human rights and Costa Rica’s best traditions of solidarity, and will affect hundreds of thousands of Nicaraguan migrants.